COMMUNICATION CHALLENGES OF MOBILE BANKING USERS IN ASUMBI TEACHERS TRAINING COLLEGE, KENYA - Titus Taro., ABONGO (IJRDO - Journal of Social Science and Humanities Research, 2017)
The purpose of this study was to determine communication challenges of mobile banking users in Asumbi Teachers Training College, Kenya. The study was conceived due to the fact that service users kept loosing funds to incorrect M-bank accounts due to lack of knowledge, no communication constantly was flowing from the service providers to inform them of changes in charges rates. The study was guided by Nora C. Quebrals’ (1989) theory which postulates that development communication is the art of Science of human communication applied to speedy transformation of a community and the mass of its people from poverty to a dynamic socioeconomic growth. The population targeted were the students and the tutors. Simple random sampling technique was employed in this study. Data was collected using questionnaires. The study employed the test retest method to do a pilot study in 2 colleges that was not part of the sample used in the final data collection. Cronbach’s alpha was used to measure internal consistency ("reliability") of the instrument the r value of 0.72 was realized, hence reliable. The study involved 53 tutors and 291 students. The study established that 87.8 percent either occasionally or several times met m-banking communication challenges of various kinds. The study also revealed that, the respondent occasionally failed to receive information communicated on M- banking promptly. The study recommended the need for in-service programmes for adult tutors who did not get opportunity to learn computer and communication skills in Kenya.